“Flavescence dorée” impacts growth, productivity and ultrastructure of Vitis vinifera plants in Portuguese “Vinhos Verdes” region - Oliveira, Manuel J. R. A. (2019)
“Flavescence dorée” (FD) is a quarantine disease associated with the presence of a phytoplasma transmitted by the insect vector Scaphoideus titanus. This disease affects grapevines and is of a great concern to the stability and sustainability of the wine industry, due to the harvest losses and death of infected plants. In Portugal, FD has seriously affected the “Vinhos Verdes” region, but so far the research on this topic is very limited. The current study confirmed that the FD phytoplasma strain involved in the outbreak in Vitis vinifera cv. Loureiro belongs to the 16SrV-D subgroup and shows very low RFLP variability in the tuf and secY genes. Transmission electron microscopy analysis of leaf midribs from infected grapevine plants revealed that the shape and structure of phloem cells were altered, presenting collapsed cells, callose accumulation in sieve plates and lipid accumulation in chloroplasts of phloem parenchyma cells. Moreover, data from two subsequent years showed that FD presence was associated with an average delay of 10 to 15 days on the time to visible inflorescences and to veraison, compared to healthy plants. At veraison, FD also lead to a significant decrease in the budburst percentage (7% to 12%), fertility index (35% in 2015), leaf area (56% to 63%), and chlorophyll content (18% to 35% lower SPAD values). Hence, infected plants showed a drastic reduction in the yield, corresponding to a decrease between 51% and 92% compared to healthy plants, which mostly resulted from a lower number of bunches (63% to 92% less), but also a decreased bunch weight (35% lower in 2015). Concerning berry quality, there were no significant differences in terms of total soluble solids and titrable acidity in both years. Here, this study concluded that the FD infection delays the grapevine development and leads to drastic production losses, which may be partly linked to the ultrastructural modifications observed in the phloem cells of infected plants.